Students' Creative Thinking Skills on Reaction Rate Topic through Contextual Teaching and Learning Model - Mangara Sihaloho; Ika Riyana Tungkagi; Netty Ino Ischak; Dewi Budi Purwati; Akram La Kilo (Jurnal Tadris Kimiya, 2022)
This research aims to analyze the contextual teaching and learning (CTL) model on students' creative thinking skills on the reaction rate topic. This quantitative research used true experimental design of pretest-posttest control. The samples used in this study were from 11th grade at SMA Negeri 1 Pinolosian. The experimental class sample was given treatment of the CTL learning model while the control class used conventional learning, respectively, were 31 and 30 students of 93 populations. Based on a questionnaire, students' creative thinking skills were obtained through observation during the learning process. The data analysis of the test instrument was carried out through a validity test using the product-moment correlation technique (significant level = 0.05), Lilliefors normality test, homogeneity of variance test and ttest. The CTL implementation questionnaire and instrument test data were converted into percentages and categorized. The results showed that the application of the CTL model had a positive effect on students' creative thinking abilities, evidenced by the average score of students in the experimental class before and after treatment increased from 14.55 to 74.84. Otherwise, in the control class, the scores were 30.59 to 33.56. The percentage of students' achievement in creative thinking aspects in the experimental class was good (61%-80%) while the control class was less good (21%-40%). The creative thinking abilities of both classes are very different, which is also reflected in the learning outcomes. The value of tcount (2.240) was greater than ttable (2.042) at the significant level = 0.05, and the hypothesis of H0 was rejected, or H1 was accepted. The application of the CTL learning model positively influenced students' creative thinking skills on the reaction rate material. Students' low originality abilities compared to fluency, flexibility, and elaboration abilities were also discussed.